The Influence of Brand Image, Price Perception and Product Quality on Skintific Skincare Purchase Decisions at Selly Cosmetics Aek Kota Batu - Triani, Triani; Elvina, Elvina (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The purpse of this study is to determine the influence of brand image, price perception, and product quality on purchasing decisions for Skintific skincare at Selly Kosmetik Aek kota Batu. The study uses a quantitative approach with an associative research type. Data collection uses a questionnaire with the help of SPSS 26. This study indicates that there is a positive and significant influence of brand image and product quality partially on purchasing decisions, while price perception has a significant effect with a negative relationship direction. Simultaneously, brand image, price perception, and product quality have a significant effect on purchasing decisions with a coefficient of determination of 57.5% while the rest is influenced by other factors outside the study. These findings indicate that brand image and product quality factors are more dominant in influencing consumer interest in purchasing Skintific skincare at the local retail level.